2017
DOI: 10.1177/0956797617698138
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intrinsic Motivation and the Satisfaction of Basic Psychological Needs Under Conditions of Severe Resource Scarcity

Abstract: An emerging field of research is beginning to examine the ways in which socioeconomic disparities affect emotional, cognitive, and social processes. In this study, we took a two-step approach to examining the role that resource scarcity plays in the predictive power of intrinsic motivation on school attendance, as well as its influence on the precursors of intrinsic motivation: the psychological needs of relatedness, autonomy, and competence. Results revealed that intrinsic motivation predicts school attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…A large body of empirical research has accounted for relations between basic need satisfaction and intrinsic motivation, coping, and positive emotions in adults as well as adolescents across different life domains [19][20][21]. In accordance with SDT´s claim for universality, a growing amount of studies has found evidence for its cross-cultural applicability in different cultures on every continent [22][23][24][25][26]. Moreover, SDT has repeatedly been applied in the educational context, and beneficial outcomes among students have effectively been targeted [27][28][29].…”
Section: Adolescent Well-being and Basic Psychological Need Satisfactionmentioning
confidence: 99%
“…A large body of empirical research has accounted for relations between basic need satisfaction and intrinsic motivation, coping, and positive emotions in adults as well as adolescents across different life domains [19][20][21]. In accordance with SDT´s claim for universality, a growing amount of studies has found evidence for its cross-cultural applicability in different cultures on every continent [22][23][24][25][26]. Moreover, SDT has repeatedly been applied in the educational context, and beneficial outcomes among students have effectively been targeted [27][28][29].…”
Section: Adolescent Well-being and Basic Psychological Need Satisfactionmentioning
confidence: 99%
“…The question of whether this premise holds under conditions where individuals' physical needs are not satisfied on a daily basis has, however, not yet been answered conclusively. Based on Basic Psychological Need Theory (BPNT) and Self‐Determination Theory (SDT's) universality claim, we expect that the satisfaction of the needs for relatedness, competence and autonomy positively contribute to the likelihood that girls engage in the self‐regulated behaviour of school attendance (also see Van Egmond et al, ).…”
Section: Basic Psychological Need Theorymentioning
confidence: 99%
“…This makes it characteristic of the living conditions of a significant part of the world's population as over 10% of the world's population (767 million people) live under the poverty line of $1.90 per day (The World bank, ). There is an emerging field of research that is beginning to examine the ways in which adverse contexts affect developmental outcomes (e.g., Ellis, Boyce, Belsky, Bakermans‐Kranenburg, & Van IJzendoorn, ; Haushofer & Fehr, ; Van Egmond, Navarrete Berges, Omarshah, & Benton, ). In the current study, we connect to this line of research and examine the main premises of two sub‐theories of self‐determination theory: Organismic Integration Theory (OIT) and Basic Psychological Needs Theory.…”
mentioning
confidence: 99%
“…Therefore, SDT may be especially relevant to populations with scarce resources. When resources are scarce, people are less able to get their needs of competence, autonomy, and relatedness met (16).…”
Section: Introductionmentioning
confidence: 99%